Results of 10 years of pre-participation cardiac screening of elite athletes in New Zealand - Orchard, J.; Davis, A.; Puranik, R.; Isbister, J.; La Gerche, A.; Driscoll, T.; Doughty, R.; Hamilton, B. (Heart Lung and Circulation, 2023)
Background Athlete cardiac screening for conditions associated with sudden cardiac death is recommended by international bodies. High Performance Sport New Zealand (HPSNZ) commenced screening elite Olympic-sport athletes in 2012.